Meningkatkan Hasil Minat Belajar Matakuliah MYOB Dengan Media Vlog Pada Mahasiswa INSTIKI - Wulantari, Ni Putu Ayu Siska; Pramawati, I Dewa Ayu Agung Tantri; Mulyawan, I Putu Arya (Cattleya Darmaya Fortuna, 2024)
The implementation of the use of the MYOB application in computerized accounting learning for INSTIKI students provides great benefits in improving their understanding of accounting reports. Through the use of this application, students can practice the theoretical concepts learned in class directly in a real environment. The purpose of this study is to find out the learning media that students like and develop Vlog-based MYOB Accounting learning management. This research was conducted at INSTIKI with the subject of 60 students who have taken MYOB courses. This research lasted for about 8 months. The method used is descriptive qualitative research, which allows for the adjustment of opinions between researchers and informants. Data collection is carried out through observation, surveys, and documentation. The results of this study stated that video tutorials are the most preferred and considered the most satisfying learning media, with the greatest influence on material understanding; Most agree vlogs help understand the material and make learning more engaging; Most are satisfied with the use and quality of the vlog; Helps remember MYOB concepts and increases interest in learning. More than half of respondents believe vlogs can replace face-to-face learning methods.